Essays on trade policy in Arab League countries - Benaddi, Atika (Kansas State University, 2019)
This dissertation consists of three essays which use the Arab League countries as a natural setting for empirical research quantifying the effects of different features of this region’s trade policies on member countries. The first essay examines the effects of the different features of the Arab League’s trade policy (preferential trade agreements, market power, and bound tariffs) on the multilateral tariffs applied by its member countries. Overall, our results suggest that preferential agreements have a building block effect on multilateral tariffs because Arab League members tend to lower their applied Most-Favored Nations (MFN) tariffs as they grant enhanced preferential access to their partners. Unlike earlier studies, we find that the formation of a customs union (CU) among Arab League members led to the same degree of external trade liberalization than forming a free trade area (FTA). Moreover, we find that high degree of importer market power tends to mitigate the building block effect of forming preferential trade agreements. The second essay investigates the effects of trade policy uncertainty on the entry decisions of exporters to Arab League markets. Using a product-level dataset on World Trade Organization (WTO) members exporting to Arab League countries for the years 1998-2015, we provide empirical evidence that trade policy uncertainty, a result of significant gaps between tariff bindings and applied tariffs (tariff water), led to the reduced entry of exporters in Arab League markets. We then extend our analysis to investigate the effects of policy uncertainty combined with additional uncertainty related to falling incomes associated with the 2007-2010 worldwide economic downturn. Our results suggest that this macroeconomic shock has contributed to a considerably more uncertain economic environment, thereby affecting the decision to enter these markets. We also analyze exporter decisions to enter new markets when the Arab League importing country exhibits high levels of market power. We find empirical evidence confirming that the effects of uncertainty on entry are magnified in the presence of high levels of market power. The third essay examines the effects of trade preferences granted by members of the Arab League on these countries’ international import prices. According to the international trade literature, preferential trade agreements (PTAs) lower trade barriers on imported goods from preferential partners, leading to consumer gains from better quality products, lower prices for existing products, and deteriorating terms of trade of the importing country relative to preferential partners. Using product-level data from 1998-2011 with information on quality-adjusted international import price indexes, applied MFN tariffs, preferential tariffs, and market power for eleven Arab League countries, we estimate the international import price effects of trade agreements formed by Arab League countries. We find that a one percentage point decrease in applied MFN tariffs leads to a fall in international import prices of about 0.16 percentage points, while domestic prices of imported goods, as well as those produced domestically if they are homogeneous, would fall by 0.84 percentage points. We also find that a one percentage point decrease in preferential tariffs leads to 0.084 percentage point increase in international prices, while domestic prices of imported goods decrease by 0.92 percentage points. Moreover, we find no significant effects of MFN tariffs and preferential tariffs on international import prices under a customs union. Furthermore, our results provide no evidence that market power affects this measure, the international import price index, of terms of trade.
Keywords: MFN tariffs; terms of trade; import price index; export supply elasticity; regionalism; trade liberalization; tariff water; trade policy uncertainty; bound tariffs; tariff water; market power; trade agreementspreferential trade agreements